Distinct Contribution of Global and Regional Angiotensin II Type 1a Receptor Inactivation to Amelioration of Aortopathy in Tgfbr1M318R/+ Mice - Bramel, Emily E.; Bagirzadeh, Rustam; Saqib, Muzna; Creamer, Tyler J.; Espinoza Camejo, Wendy A.; Roker, LaToya Ann; Pardo Habashi, Jennifer; Dietz, Harry C.; Gallo MacFarlane, Elena (Frontiers in Cardiovascular Medicine, 2022)
Angiotensin II (Ang II) type 1 receptor (AT1R) signaling controls both physiological and pathogenetic responses in the vasculature. In mouse models of Loeys-Dietz syndrome (LDS), a hereditary disorder characterized by aggressive aortic aneurysms, treatment with angiotensin receptor blockers (ARBs) prevents aortic root dilation and associated histological alterations. In this study we use germline and conditional genetic inactivation of Agtr1a (coding for the AT1a receptor) to assess the effect of systemic and localized AT1R signaling attenuation on aortic disease in a mouse model of LDS (Tgfbr1M318R/+). Aortic diameters and histological features were examined in control and Tgfbr1M318R/+ mice with either germline or Mef2CSHF-Cre mediated genetic inactivation of Agtr1a, the latter resulting in deletion in second heart field (SHF)-derived lineages in the aortic root and proximal aorta. Both systemic and regional AT1R signaling attenuation resulted in reduction of diameters and improvement of tissue morphology in the aortic root of LDS mice; these outcomes were associated with reduced levels of Smad2/3 and ERK phosphorylation, signaling events previously linked to aortic disease in LDS. However, regional AT1a inactivation in SHF-derived lineages resulted in a more modest reduction in aortic diameters relative to the more complete effect of germline Agtr1a deletion, which was also associated with lower blood pressure. Our findings suggest that the therapeutic effects of AT1R antagonisms in preclinical models of aortic disease depend on both regional and systemic factors and suggest that combinatorial approaches targeting both processes may prove beneficial for aneurysm mitigation.